Chemical and Biological Threats, Hazard Potential and Countermeasures - Korabecny, Jan; Soukup, Ondrej (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this Special Issue of Toxics entitled, "Chemical and biological threats, hazard potential and countermeasures". In this special issue we would like to pay attention to various aspects of toxicology specifically focused on the chemical and biological threats, which may accidentally or on purpose endanger human health. Besides the characterization of such threats and their biological consequences we will focus on the available and novel experimental countermeasures capable to protect from and/or threat such exposures.